Pentingnya Pendidikan Demokrasi dan Hak Asasi Manusia di Dunia Pendidikan - rinayang; Musafir; Mulyono, Ana; Dewi, Fita Umaya; Rahmah, Feru Nika Tiana; Qahfi, Lalu Ashabul; Aolia, Nazia; Bagus, Raden; Gunawan, Hari; Zazuli, Ahmad Aditian; Juliadi, Juliadi; Yanti, Hastika; Firdaus, Fahmi; Azizi, Faziyatul (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
Democracy and human rights (HAM) education are important components in building a just and civilized society. In the context of the world of education, a strong understanding of the principles of democracy and human rights not only strengthens individual character, but also increases social and political awareness. This article discusses the importance of integrating democracy and human rights education in the education curriculum, as well as its impact on forming a generation that is aware of their rights and obligations as citizens.